2021
DOI: 10.1108/apjml-08-2020-0570
|View full text |Cite
|
Sign up to set email alerts
|

The synergistic impact of motivations on sustained pro-environmental consumer behaviors: an empirical evidence for single-use plastic products

Abstract: PurposeThis paper employed the self-determination theory (SDT) to examine the synergistic impacts of intrinsic, extrinsic and prosocial motivations in promoting sustained pro-environmental consumption behaviors (PECB). To provide evidence for the study’s theoretical framework, the authors focus on the behavior of reducing single-use plastics.Design/methodology/approachA mall-intercept survey for consumption of single-use plastic products in three big cities of Vietnam (Hanoi, Da Nang and Ho Chi Minh city) was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 70 publications
0
18
1
Order By: Relevance
“…Pro-environmental consumption behavior is one of the central topics of current marketing literature, especially in the context of Western economies (Nguyen et al. , 2018; Pham et al , 2021). Currently, with the rising number of environmental concerns worldwide, especially in emerging Asian economies, sustainable consumption has been becoming the cutting edge of consumer behavior research (Quoquab et al.…”
Section: Conclusion Implications Further Directionsmentioning
confidence: 99%
See 3 more Smart Citations
“…Pro-environmental consumption behavior is one of the central topics of current marketing literature, especially in the context of Western economies (Nguyen et al. , 2018; Pham et al , 2021). Currently, with the rising number of environmental concerns worldwide, especially in emerging Asian economies, sustainable consumption has been becoming the cutting edge of consumer behavior research (Quoquab et al.…”
Section: Conclusion Implications Further Directionsmentioning
confidence: 99%
“…When women are motivated to carry out pro-environmental behavior, it is easier for them to purchase environmentally friendly products (Sreen et al, 2018). (Nguyen et al, 2018;Pham et al, 2021). Currently, with the rising number of environmental concerns worldwide, especially in emerging Asian economies, sustainable consumption has been becoming the cutting edge of consumer behavior research (Quoquab et al, 2019).…”
Section: Structural Path Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…According to the findings of several studies, intrinsic and extrinsic motivation has been demonstrated to have both a direct and a mediating effect on PEB (Afsar et al, 2016;Cecere et al, 2014). These investigations were carried out in a range of different environments and involved a number of different participants (Cheung et al, 2017;Ofori and Opoku Mensah, 2021;Pham et al, 2021). Thus, we propose: H1.…”
Section: Conceptual Model and Hypothesis Developmentmentioning
confidence: 95%